High level of PD-1 expression on hepatitis C virus (HCV)-specific CD8+ and CD4+ T cells during acute HCV infection, irrespective of clinical outcome. - Kasprowicz, V; Schulze Zur Wiesch, J; Kuntzen, T; Nolan, B; Longworth, S; Berical, A; Blum, J; McMahon, C; Reyor, L; Elias, N; Kwok, W; McGovern, BG; et al. (2008)
We monitored expression of PD-1 (a mediator of T-cell exhaustion and viral persistence) on hepatitis C virus (HCV)-specific CD8(+) and CD4(+) T cells from blood and liver during acute and chronic infections and after the resolved infection stage. PD-1 expression on HCV-specific T cells was high early in acute infection irrespective of clinical outcome, and most cells continued to express PD-1 in resolved and chronic stages of infection; intrahepatic expression levels were especially high. Our results suggest that an analysis of PD-1 expression alone is not sufficient to predict infection outcome or to determine T-cell functionality in HCV infection.